Mobility choices and climate change: Assessing the effects of social norms, emissions information and economic incentives. (December 2021) - Raux, Charles; Chevalier, Amandine; Bougna, Emmanuel; Hilton, Denis
Abstract: The potential of psychological and fiscal framing interventions in motivating environmentally responsible behavior is explored in a context of long distance leisure travel. A series of discrete choice experiments is conducted with 789 participants. Framing conditions like information on CO2 emissions, an injunctive and a descriptive norm, fiscal incentives such as a carbon tax, a bonus-malus and a personal carbon trading scheme are tested while controlling the usual travel price-duration tradeoff. Pricing (including internalization of social cost of CO2 through fiscal incentives) has the expected effect of reducing the choice of travelling and hence CO2 emissions. Providing information on CO2 emissions of each transport alternative significantly reduces preferences for the most emitting modes (air) and favors a less emitting mode (train). Framing the fiscal incentive as personal carbon trading adds a moderate incentive to the price effect in reducing air choice. Highlights: Explore changes in stated choices behavior for long distance leisure travel. Assess the potential of informational, psychological and fiscal framings. Analysis based on an online experiment with six treatments and 789 participants. Providing information on CO2 emissions has a significant influence. Framing the fiscal incentive as personal carbon trading adds effectiveness.